1994
DOI: 10.1037/0096-1523.20.4.709
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and kinematic properties of motor behavior reflected in mentally simulated action.

Abstract: Related perceptual, motor, and cognitive performances were examined to reveal the accuracy of the properties of action spontaneously represented when mentally simulating moving one's hand. The kinematic configuration of the body represented and transformed in mental simulations was not fixed or canonical but corresponded to one's current configuration. Mental simulation time mimicked movement time for natural efficient movement from a posture midway between each of the hand's joint limits into many other postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

64
766
4
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 532 publications
(847 citation statements)
references
References 69 publications
64
766
4
13
Order By: Relevance
“…He concluded that movements performed mentally would induce motor imagery and would therefore be constrained by anatomical joint characteristics in a similar way as real movements [14]. The use of motor imagery strategies in mental rotation of hands has been corroborated by many authors [e.g., 9,14,23]. Evidence for motor imagery being involved in mental rotation of body parts comes from clinical cases [e.g., 3,4,12,16] and from neuroimaging studies (see [22] for review).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…He concluded that movements performed mentally would induce motor imagery and would therefore be constrained by anatomical joint characteristics in a similar way as real movements [14]. The use of motor imagery strategies in mental rotation of hands has been corroborated by many authors [e.g., 9,14,23]. Evidence for motor imagery being involved in mental rotation of body parts comes from clinical cases [e.g., 3,4,12,16] and from neuroimaging studies (see [22] for review).…”
Section: Introductionmentioning
confidence: 98%
“…Using a handedness paradigm in which participants had to decide if a displayed hand was a right or left one, Parsons [13,14] showed that RTs were not only influenced by the rotation angle of the hand stimulus but also by the implicit awkwardness of the displayed hand position. He concluded that movements performed mentally would induce motor imagery and would therefore be constrained by anatomical joint characteristics in a similar way as real movements [14]. The use of motor imagery strategies in mental rotation of hands has been corroborated by many authors [e.g., 9,14,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People tend to use egocentric transformations when hands are mentally rotated [7,30,38], recruiting motor processes and structures in the process [11]. Subjects imagine moving their own hands from their actual posture into that of the stimulus for comparison [31], and thus the position of subject's own hands plays an important role in the ability to mentally manipulate hands in space [11,33,40]. Indeed, the effect of postural constraints is body part specific in that placing one's hands behind the back impairs the mental rotation of hands but not of feet [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, neurovegetative activation during physical effort is proportional to that measured during the mental simulation of the same task [12] and different cerebral lesions may determine selective and dissociable imagery deficits [41]. Given the stability of temporal and kinematic characteristics of real and sim-ulated movements, it is reasonable that the same properties guide both execution and simulation of the same movement [1,13,31]. In this way mental rotation (a class of mental imagery tasks) can be considered a good tool to study motor representations.…”
Section: Introductionmentioning
confidence: 99%